Geothermal power plant as a sustainable renewable energy alternative: Innovations and engineering solutions - Saputra, Dany Yuda; Sibarani, Saputra (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Indonesia is an area that has abundant geothermal energy availability, with a total of approximately 28,617 MW. This is because Indonesia is located on the ring of fire between the Atlantic and Pacific oceans. However, this availability does not automatically make Indonesia prioritize geothermal power plants (GPP) as a substitute for fossil fuels in the future. GPP only ranks third in priority below hydropower plants (PLTA) and biomass power plants (PLT Biomasa). The purpose of this study is to look at the strengths, weaknesses, opportunities, and threats of geothermal energy supply. This article uses a qualitative method with literature review and SWOT analysis to describe the phenomenon experienced by geothermal energy in Indonesia. Methods: This article uses a qualitative method with literature review and SWOT analysis to describe the phenomenon experienced by geothermal energy in Indonesia. Findings: The results of this study show that geothermal energy has strengths, namely reliable, stable, and efficient power, a clean energy with minimal emissions, does not require storage space, does not require large land and has minimal water requirements, and provides direct benefits to the community. Meanwhile, the weaknesses of geothermal energy utilization are that it has a relatively high investment cost, requires sophisticated and complex technology, so it takes a long time to develop, is highly dependent on geographic location to obtain good capacity, is sometimes far from the load center, often conflicts with indigenous communities, making it difficult to obtain social license, and has negative impacts on flora and fauna. The opportunity to utilize this technology is the existence of regulations, especially Law No. 21/2014 and other related regulations, including as the third potential renewable energy transition. The threats faced are government policies and licensing processes that still do not fully support geothermal energy, international scrutiny, and community resistance. Conclusion: The conclusion of this article is that geothermal energy is very suitable as a substitute for fossil fuels by mitigating and improving policy, technology, and financing aspects. Novelty/Originality of this article: The originality of this article lies in its application of a SWOT analysis to evaluate the geothermal energy sector in Indonesia. It provides a comprehensive review of the current challenges and opportunities in utilizing geothermal energy as a renewable resource, highlighting the need for policy improvements and technological advancements to overcome barriers and support its growth.